The Use of Membranes (ST-100, oXiris, and M60) for Continuous Renal Replacement Therapy in a Child with Sepsis - Jiayun Ying; Xiaodi Cai; Guoping Lu; Weiming Chen (Case Reports in Critical Care, 2023)
Sepsis is a critical condition affecting patients worldwide. Systemic inflammatory response syndrome in sepsis contributes to organ dysfunction and mortality. The oXiris is a recently developed continuous renal replacement therapy (CRRT) hemofilter indicated for the adsorption of cytokines from the bloodstream. In our study, in a septic child, CRRT with three filters, including the oXiris hemofilter, resulted in a downregulation of inflammatory biomarkers and a reduction of vasopressors. Herein, we described the first report of such usage in septic children.